1966
DOI: 10.2307/3479385
|View full text |Cite
|
Sign up to set email alerts
|

Negligence without Fault

Abstract: Four children chasing a kite drowned in a frozen pond.Y Damages were sought from a railroad company by whose admitted negligence water had been diverted to form the fatal pond. The Supreme Court of Pennsylvania denied liability because a prudent man in the defendant's place could not have "anticipated and foreseen this unfortunate happening" and because "there was no breach of duty to the children." 2 Jury verdict, majority opinion, and dissent reflect the uncertainty and t Copyright, 1951, The Regents of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…See, e.g., McBride 2004: 425-26;Bender 1988: 30-31. 4 See, for example, Abraham 2012: 288;Ehrenzweig 1966Ehrenzweig : 1431Ehrenzweig -32, 1435Ehrenzweig , 1444Gregory 1951: 380-84. (2019) 37 journal for constitutional theory and philosophy of law Do societies prioritize harm prevention?…”
Section: Tort Law and The Priority Of Harm Preventionmentioning
confidence: 99%
“…See, e.g., McBride 2004: 425-26;Bender 1988: 30-31. 4 See, for example, Abraham 2012: 288;Ehrenzweig 1966Ehrenzweig : 1431Ehrenzweig -32, 1435Ehrenzweig , 1444Gregory 1951: 380-84. (2019) 37 journal for constitutional theory and philosophy of law Do societies prioritize harm prevention?…”
Section: Tort Law and The Priority Of Harm Preventionmentioning
confidence: 99%
“…In one important article, he advocated liability for "the unavoidable and insurable consequences of lawful (enterprise) activities." 59 For him, so long as the harm was "typical" for the activity and "thus calculable and reasonably insurable" 60 the enterprise should be liable in tort. He called this "negligence without fault" and justified imposing the duty of compensation on the enterprise on the ground that "these liabilities are the price which must be paid to society for the permission of a hazardous activity."…”
Section: A Francis Bohlen's "Benefit" Theorymentioning
confidence: 99%
“…The Columbia report suggested that compensation should be paid from a general fund and that accident losses should be spread over a large population with a view to providing appropriate compensation to the maximum number of victims. 13 See, e.g., Ehrenzweig (1951;1955) and Green (1958). …”
mentioning
confidence: 99%